Written representation of spoken interaction in the official parliamentary transcripts of the Finnish Parliament - Voutilainen, Eero (Frontiers in Communication, 2023)
In this article, I will analyze the written representation of spoken interaction in the official plenary session transcripts of the Finnish Parliament. The official parliamentary transcripts are not – and cannot be – identical copies of the original speech event. Instead, they are linguistically and textually edited in many ways. I will examine the different types of editorial changes that are made in the official Finnish parliamentary transcripts. These include phonological, morphological and syntactic alterations, editing out of self-repairs, planning expressions, stuttering and slips-of-tongue, and finding written ways of expression for phenomena such as pauses, prosody, gestures and non-verbal events. I will also discuss how the editorial changes affect the written representation of plenary session interaction.